2003
DOI: 10.1097/00000542-200311000-00027
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Spinal Prostaglandin Synthesis Early after L5/L6 Nerve Ligation Prevents the Development of Prostaglandin-dependent and Prostaglandin-independent Allodynia in the Rat

Abstract: The results of this study provide solid evidence that spinal prostaglandins, synthesized by cyclooxygenase-1 in the first 4-8 h after ligation, are critical in the pathogenesis of prostaglandin-dependent and prostaglandin-independent allodynia and that their early pharmacologic disruption affords protection against this neuropathic state in the rat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 48 publications
0
29
1
Order By: Relevance
“…A host of other studies have demonstrated the efficacy of NSAIDS in a variety of NMDA sensitive pain models (Ghilardi et al, 2004;Matsunaga et al, 2007) (Hefferan et al, 2003;Ren and Dubner, 1993;Ren et al, 1992b;Zhao et al, 2000) (Malmberg and Yaksh, 1993a) (Dirig et al, 1998). Taken together, these data strongly imply that products of cyclooxygenase activation (prostanoids) are frequently downstream of NMDA receptor activation in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…A host of other studies have demonstrated the efficacy of NSAIDS in a variety of NMDA sensitive pain models (Ghilardi et al, 2004;Matsunaga et al, 2007) (Hefferan et al, 2003;Ren and Dubner, 1993;Ren et al, 1992b;Zhao et al, 2000) (Malmberg and Yaksh, 1993a) (Dirig et al, 1998). Taken together, these data strongly imply that products of cyclooxygenase activation (prostanoids) are frequently downstream of NMDA receptor activation in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, peripheral nerve injury induces an up-regulation of COX-1 and COX-2 in the spinal cord and peripheral nerves during the early phase of neuropathic pain development (Hefferan et al, 2003;Ma and Eisenach, 2002;Zhao et al, 2000). Furthermore, CCI in rats reduces glutamate transporter uptake activity in the spine, as well as increasing extracellular concentrations of arachidonic acid and glutamate (Sung et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown the usefulness of acute or repetitive administration of indomethacin [Zhao et al, 2000;Takahashi et al, 2004] S-ibuprofen, SC-560 [Hefferan et al, 2003], naproxen [Padi and Kulkarni, 2004], and meloxicam [Takahashi et al, 2005] when drugs are given before or immediately after nerve injury. Accordingly, several studies have found that intrathecal injection of ketorolac, piroxicam, NS-398 [Lashbrook et al, 1999], indomethacin [Zhao et al, 2000], S-ketoprofen [Ossipov et al, 2000], rofecoxib [Padi and Kulkarni, 2004], and meloxicam [Takeda et al, 2005] does not reverse established neuropathic pain in rats.…”
Section: Antiallodynic Effect Of Metamizolmentioning
confidence: 99%